蜗轮蜗杆副的空间操作器应用研究 - 朱映远; 倪风雷; 刘宏 (Jixie chuandong)
For the new development of robot in the space,a compact and dependable machine should be used in the robot manipulator.It is fit for worm gearing used as the driver to grasp for the advantage of simple motion and drive direction which could be changed.Aiming to overcome the worm gearing adaptability problem in the space,the install,lubrication,libration,temperature and using life of the worm gearing used in the space manipulator are researched by analysis and experiments.The manipulator constituted with worm gearing is tested in the space environment simulated by the thermal vacuum chamber and vibration table.The results indicate that worm gearing can fit for the space use.